PENERAPAN METODE SAS BERMEDIA KARTU BERGAMBAR AKTIVITAS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK AUTIS DI SDLB - HADI KUSUMA WARDANI, ERMA (Jurnal Pendidikan Khusus, 2017)
ABSTRACT                                                                              Autistic children in grade 2 and 3 in SDLB Krida Utama 2 Loceret Nganjuk not able to read well. When receiving reading lessons, the child can only read a few letters, a less obvious syllable, and read a non-fluent word. Children need to get guidance so they can read letters, syllables, words and sentences well. The purpose of this research is to know the application of method of sas picture card media activity to improve the reading ability of children with autism in SDLB Krida Utama 2 Loceret Nganjuk. This research uses quantitative approach with Pre-Experimental research type using One Group Pretest Posttest Design research design. The results showed a visible improvement of early reading ability of children through developed aspects of knowing and pronouncing words, spelling syllables, spelling words, and connecting sentences. This is evidenced by the results of data analysis showing the value of Z value = 2.04 bigger than the value of Z table = 1.96 which means the improvement of reading ability through the application of sas method with picture card media activity in SDLB Krida Utama 2 Loceret Nganjuk.   Keywords: sas method, picture card media, start reading capability.